Agricultural price policy- the context and the approach - Ahmed, Raisuddin; Mellor, John W. (International Food Policy Research Institute, 1988)
Determination of agricultural prices is intensely political because of its profound influence on equity, income distribution, consumption, production, and economic development. Thus agricultural price policy occupies a major place in political debate, the deliberations of government bureaucracies, and the decisions made by consumers and producers. This is so in both high-income countries, where food and agriculture represent a small part of aggregate income but are still important in consumption and politics, and in low-income countries, where they are central to the political and economic processes.